Public Systems Modeling Methods for Identifying and Evaluating Alternative Plans and Policies - Loucks, Daniel P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This is an open access book discusses readers to various methods of modeling plans and policies that address public sector issues and problems. Written for public policy and social sciences students at the upper undergraduate and graduate level, as well as public sector decision-makers, it demonstrates and compares the development and use of various deterministic and probabilistic optimization and simulation modeling methods for analyzing planning and management issues. These modeling tools offer a means of identifying and evaluating alternative plans and policies based on their physical, economic, environmental, and social impacts. Learning how to develop and use the mathematical modeling tools introduced in this book will give students useful skills when in positions of having to make informed public policy recommendations or decisions.
1. Analyzing Public Policy Decisions -- 2. Public Sector Systems -- 3. Creating Models -- 4. Modeling Examples and Solutions -- 5. Models for Managing Money -- 6. Solving Models Using Excel -- 7. Discrete Optimization Modeling -- 8. Linear Optimization Modeling -- 9. Some Linearization Methods -- 10. Solving Models Using Calculus -- 11. Lagrangian Models -- 12. Dealing with Uncertainty -- 13. Modeling Stochastic Processes -- 14. Chance Constrained and Monte Carlo Modeling -- 15. Simulation Modeling -- 16. Multi Criteria Analyses -- 17. Fuzzy Optimization -- 18. Conclusions.
Keywords: Political planning; Operations research; Mathematical optimization; Econometrics; Public administration; Public Policy; Operations Research and Decision Theory; Optimization; Quantitative Economics; Public Management; Policy Evaluation